Two novel pathogenic variants in KIAA1109 causing Alkuraya-Kučinskas syndrome in two Czech Roma brothers. Issue 4 (October 2020) - Meszarosova, Anna Uhrova; Lastuvkova, Jana; Rennerova, Ladislava; Hitka, Patrik; Cihlar, Filip; Seeman, Pavel; Safka Brozkova, Dana
Abstract : Recently described Alkuraya-Kučinskas syndrome (ALKKUCS) clinically presented with severe congenital hydrocephalus, severe brain hypoplasia and other multiple malformations has been described in only few families worldwide to date. ALKKUCS is caused by biallelic pathogenic variants in the KIAA1109 gene with autosomal recessive inheritance. We describe two brothers of Roma origin born with severe congenital hydrocephalus, brain hypoplasia and other clinical findings corresponding with ALKKUCS. Using WES two novel pathogenic variants c.359-1G>A and c.14564_14565del in compound heterozygous status in the KIAA1109 gene were found in both brothers. We consider that the number of healthy heterozygous carriers of pathogenic variants in KIAA1109 could be higher than it is known and pathogenic variants in KIAA1109 could be more frequent cause of congenital hydrocephalus and severe brain dysplasias.